Lead sorption by carbon nanofibers grown on powdered activated carbon — kinetics and equilibrium - Al-Mamun, Abdullah; Al-Khatib, Ma An Fahmi Rashid; Jameel, Ahmed Tariq (World Scientic Publishing Company, 2015)
Carbon nano¯bers (CNFs) were synthesized by using a safe and less hazardous method, compared to using °oating catalysts in chemical vapor deposition (CVD) process. This process used C2H2 as carbon source and oil palm kernel shell-based powdered activated carbon (PAC) as cheap solid substrate. Use of nickel (Ni2þ) impregnated PAC as ¯xed substrate for the synthesis of CNF is one of the novelties of the research work accomplished by the authors. The PAC–CNFs porous nanocomposite product was used for the sorption of lead ions (Pb2þ) from synthetic aqueous solution. Kinetics of Pb2þ adsorption and isotherms were investigated by varying initial concentration of lead and contact time. PAC–CNFs were found to remove Pb2þ better at acidic pH of about 5.5. Langmuir and Freundlich isotherms were applied to the sorption equilibrium data to ¯nd the best ¯tted model. Langmuir isotherm model with R2 ¼ 0:965 ¯tted the adsorption data better than the Freundlich isotherm. The kinetic processes of Pb2þ adsorption on CNFs were investigated by applying di®erent kinetic models, namely zero-order, pseudo-¯rst-order and pseudo-second-order. The pseudo-second-order rate equation exhibited the best results with R2 ¼ 0:999, qe ¼ 74:79 (mg/g) and K2 ¼ 0:029 (min . g=mg). The novel nanocomposite product seemed to have the potential to remove Pb2þ ions from aqueous solution.